Genetic and Phenotypic Variations in Phenylthiocarbamide Bitter Taste Receptors in Iraqi Population - Nubgan, Amer (Iraqi Journal of Science, 2023)
Bitter substances are identified by protein receptors located on surface of taste cell membranes. Mutational polymorphism of the bitter taste receptor (TAS2R38) is a significant determinant in phenylthiocarbamide (PTC) threshold perception. This research’s objectives were to find TAS2R38 polymorphisms in Iraqi people and investigate any correlations between genotype and the PTC taste sensitivity. Bitterness sensitivity was determined by assessing the capacity to differentiate and the responsiveness to a representative strip of PTC. Cheek cells samples were collected for DNA extraction, PCR amplification and genotyping. PCR was performed to amplify the short region of the TAS2R38 gene containing the initial polymorphisms of interest (145G > C, rs713598). Amplified samples were digested by the restriction enzyme (HaeIII) to study the genetic variations in TAS2R38 which is involved in PTC bitter sensitivity. This particular study included a total of 32 different cohorts. The phenotypic frequency of PTC strong-tasters and non-tasters was identical at 34.375% which was a greater value than the frequency of weak-tasters (31.25%). While genotypic data analysis showed that weak-tasters had a genotypic frequency of 45.16% which was higher than the genotypic frequencies of strong-taters (22.58%) and non-tasters (32.26%) respectively. In addition to this, 87.1% of the projected phenotypic and genotypic frequencies were in agreement with one another. Even though more detailed statistical analysis with a bigger group is needed. The results of this study suggest that allelic variation in the single locus TAS2R38 rs713598 works as a crucial genetic marker for bitterness sensitivity and has vital roles in the bitter tasting ability among Iraqi population.